Niewidzialna ręka społecznej odpowiedzialności biznesu - Kuropatwa, Alicja (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents the concept of Corporate Social Responsibility and its institutional character. On this basis, it is indicated that because of its assumptions CSR is a natural market process. Each of competitive entrepreneurs wishing to maximize their profits will attempt to meet social expectations, which means that CSR can and should be the grassroots movement, this means, without any state support, without imposing on entrepreneurs how they should function
Keywords: społeczna odpowiedzialność biznesu; biznes; pracodawca; wolny rynek